2022
DOI: 10.3390/su142417042
|View full text |Cite
|
Sign up to set email alerts
|

Development and Testing of a New UWB Positioning Measurement Tool to Assist in Forest Surveys

Abstract: Forest resource inventory is a significant part of the sustainable management of forest ecosystems. Finding methods to accurately estimate the diameter at breast height (DBH), tree height and tree position is a significant part of forest resource inventory. The traditional methods of forest resource inventory are expensive, difficult, laborious and time-consuming; the existing systems are not convenient to carry, resulting in low working efficiency. In addition, it is usually necessary to rely on a forest comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Fan et al [1] obtained a +0.33 cm bias and a 1.26 cm RMSE for tree DBH measurements using a mobile phone with a TOF camera and SLAM technology. Zhao et al [23] used a ground photogrammetry method to estimate tree DBH, and reported a rRMSE of the DBH estimates of individual trees that ranged from 3.01 to 6.43%. Liang et al [56] estimated tree DBH using a multi-single-scan TLS method in forest inventories, and reported a RMSE range from 0.90 to 1.90 cm.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Fan et al [1] obtained a +0.33 cm bias and a 1.26 cm RMSE for tree DBH measurements using a mobile phone with a TOF camera and SLAM technology. Zhao et al [23] used a ground photogrammetry method to estimate tree DBH, and reported a rRMSE of the DBH estimates of individual trees that ranged from 3.01 to 6.43%. Liang et al [56] estimated tree DBH using a multi-single-scan TLS method in forest inventories, and reported a RMSE range from 0.90 to 1.90 cm.…”
Section: Discussionmentioning
confidence: 99%
“…Tang et al [58] used a small-footprint mobile LiDAR to scan a study area, and reported a positioning accuracy better than 0.32 m in two different areas, with expensive and heavy hardware. Zhao et al [23] also used UWB technology to estimate tree positions, and reported a RMSE range from 0.07 m to 0.16 m. However, their UWB positioning method required calibration of the four corners of the plot, and each corner was placed with a UWB module. Thus, the method was complex and time-consuming.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations